IMPROVING STUDENTS' RECOUNT TEXT READING ABILITY USING ARANGGE CARD TECHNIQUE - Rindi, Rindi; Piju Yupiter (PT. Intelek Cendikiawan Nusantara, 2024)
Reading is a complex skill that involves all higher mental processes to understand what is read. Reading is one way to get information. So reading becomes an important part of our lives, because sometimes to get information people will read, for example in looking for work by reading a book and newspaper. Iwuk (2007, p.7)